Airway macrophages in health and disease - Hussell, Tracy (Henry Stewart Talks, 2014)
Regulation of airway macrophages, CD200 knockout mice, Changes in airway macrophages due to infections, Co-stimulation of macrophages, MicroRNAs in TLR signaling, TAM receptors, Hyaluronic acid in infection